Recording physiological history of cells with chemical labeling - Huppertz, Magnus-Carsten; Wilhelm, Jonas; Grenier, Vincent; Schneider, Martin W.; Falt, Tjalda; Porzberg, Nicola; Hausmann, David; Hoffmann, Dirk C.; Hai, Ling; Tarnawski, Miroslaw; Pino, Gabriela; Slanchev, Krasimir; et al. (Science, 2024)
Recordings of the physiological history of cells provide insights into biological processes, yet obtaining such recordings is a challenge. To address this, we introduce a method to record transient cellular events for later analysis. We designed proteins that become labeled in the presence of both a specific cellular activity and a fluorescent substrate. The recording period is set by the presence of the substrate, whereas the cellular activity controls the degree of the labeling. The use of distinguishable substrates enabled the recording of successive periods of activity. We recorded protein-protein interactions, G protein-coupled receptor activation, and increases in intracellular calcium. Recordings of elevated calcium levels allowed selections of cells from heterogeneous populations for transcriptomic analysis and tracking of neuronal activities in flies and zebrafish.